Steroids as treatment for glomerulonephritis: time for a rethink. Issue 7 (14th November 2020) - Hendra, Heidy; Salama, Alan D
Abstract: Glucocorticoids have been a cornerstone of treatment for inflammatory and autoimmune kidney diseases for almost 70 years, yet it is fair to say, we still do not know how 'best' to use them. Significant adverse events are associated with their continued use, which contribute to premature patient mortality. Steroid avoidance or minimization is possible and has been tested in various glomerular diseases, as a result of novel agents or innovative regimens using established therapeutics. It is now time to seriously address our use of steroids and educate physicians on better ways of managing inflammatory kidney diseases.